Variation of Schumann resonance frequency observed at Allahabad (Lat 22°N, Long 81.51°E) - Hazra, S.; Sinha, A.K.; Pathan, B.M. (My University, 2010)
The lightening bolts throughout the Earth stimulate the cavity between the Earth's surface and lower ionosphere to resonate at extremely low frequency (ELF). This causes the Earth's magnetic field to oscillate at these frequencies and the phenomenon is known as Schumann resonance (SR). Theoretically, the harmonics of the oscillations are found to be at approximate frequencies of 7.8, 14, 20, 26, 33, 39 and 45 Hz, which depend on the conductivity of the lower ionosphere, conductivity of the ground and different propagation properties of the Earth-ionosphere cavity. With the improved sensitivity, accuracy and sampling rate of the search coil magnetometer installed at low latitude (Allahabad, lat 22°N, long 81.51°E), the characteristics of SR frequency have been studied and presented.
Keywords: Schumann resonance frequency; Lightening bolt; Geomagnetic field variation